THE IMPACT OF GOVERNANCE UPON SUSTAINABLE DEVELOPMENT. EMPIRICAL EVIDENCE - BACIU, Leonina Emilia (Studia Universitatis Babeș-Bolyai Oeconomica, 2023)
This study assesses the effect of governance upon sustainable development. The trends of the Worldwide Governance Indicators (WGI) and the Sustainable Development Index (SDI) are analysed for the 2005 - 2021 period for 161 countries by using Pooled Ordinary Least Squares (OLS) estimations for panel data, the multiple regression modelling. The results emphasize the significant effect of regulatory quality, government effectiveness, political stability, rule of law, control of corruption and voice and accountability on SDI. The results of the research show that governance is a variable that should be taken into consideration for explaining sustainable development level each country may achieve. JEL Classification: C23, Q1